Clinical Decision Support for Colon and Rectal Surgery: An Overview - McCoy, Allison B.; Melton, Genevieve B.; Wright, Adam; Sittig, Dean F. (Clinics in Colon and Rectal Surgery, 2013)
Clinical decision support (CDS) has been shown to improve clinical processes, promote patient safety, and reduce costs in healthcare settings, and it is now a requirement for clinicians as part of the Meaningful Use Regulation. However, most evidence for CDS has been evaluated primarily in internal medicine care settings, and colon and rectal surgery (CRS) has unique needs with CDS that are not frequently described in the literature. The authors reviewed published literature in informatics and medical journals, combined with expert opinion to define CDS, describe the evidence for CDS, outline the implementation process for CDS, and present applications of CDS in CRS.CDS functionalities such as order sets, documentation templates, and order facilitation aids are most often described in the literature and most likely to be beneficial in CRS. Further research is necessary to identify and better evaluate additional CDS systems in the setting of CRS.
Keywords: clinical decision support systems; colorectal surgery; electronic health records; patient safety